Evolution of Metal Casting Technologies : A Historical Perspective - Khan, Muhammad Azhar Ali; Sheikh, Anwar Khalil; Al-Shaer, Bilal Suleiman (Springer International Publishing : Imprint: Springer, 2017)
This book provides an overview of metal casting technologies starting from its historical evolution to casting design strategies that are being followed today in foundries and other metal casting industries. The details of most of the casting processes and their applications are also included for completeness. Foundry practices such as mold materials and molding techniques, pattern making and cores, furnaces, pouring, cleaning and heat treatment etc. are discussed in detail. Finally, current practices in casting design are demonstrated. Further developments in the field through computational methods and virtual reality are also described.
Keywords: Materials science.; Industrial engineering.; Technology -- History.; Metals.; elektronické knihy; electronic books